The effects of income inequality on BMI and obesity: Evidence from the BRFSS - Benjamin Volland (Max Planck Institute of Economics, 2012)
Despite increasing knowledge on its adverse consequences, obesity prevalence across the U.S. has been rising markedly over the past three decades. The private and economic costs of this development are substantial, and it has been estimated that its direct and indirect costs now sum to over 1% of annual GDP. While much progress has been achieved in recent years in understanding the economic changes that contribute to this development, a little researched factor that has also been argued to exacerbate the prevalence of obesity is the distribution of income. Augmenting data from 12 consecutive waves of the Behavioral Risk Factor Surveillance System (BRFSS), with a recently published data set on state-level income inequality based on tax payments, the present paper analyzes whether changes in income inequality can be considered a determinant of variations in body mass and obesity across the U.S. It finds that they have a significant positive effect on BMI and obesity. While the effect is small, it is in the range of other state-level determinants, suggesting that some form of redistributive policy may help containing the spread of unfavorable weight outcomes.
Keywords: I14; I18; 330; BMI; obesity; income inequality; BRFSS; Einkommensverteilung; Körpergewicht; USA